A history of western music - Grout, Donald Jay 1902-1987 (Norton, 2010)
"The narrative of A History of Western Music naturally focuses on the musical works, styles, genres and ideas that have proven most influential, enduring and significant - but it also encompasses a wide range of music, from religious to secular, from serious to humorous, from art music to popular music, and from Europe to the Americas."--Publisher's description.